Answer:
it is a solvable equation
Step-by-step explanation:
(x + 2) -3(x - 4) = 6 and x = 4
if x = 4 then fill in all the x's with 4 so the equation is now:
(4 + 2) -3(4 - 4) = 6
Use PEMDAS
Now the equation is 6 - 3(0) = 6
-3 times 0 is 0 so it's 6-0=6
6 = 6
when you put the 4 in for the x variables and the numbers on both sides of the equal sign are the same it makes the equation true
hope this makes sense and hope it helps :)
Answer:
your range is 11
Step-by-step explanation:
22-11= 11
Answer:
56
Step-by-step explanation:
z varies jointly with x and y:
z = kxy
When x = 2 and y = 2, z = 7.
7 = k(2)(2)
k = 7/4
z = 7/4 xy
When x = 4 and y = 8:
z = 7/4 (4)(8)
z = 56
Answer:
0.625
Step-by-step explanation:
5/8 is the same as dividing so divide them both and it will equal 0.625
There are 99 miles left. 43(7)=301. 400-301=99.